Implementation of Simulation Models for Learning Physical Education during the COVID-19 in Banjarmasin - Rahmadi, Tri Irianto, Jarudin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is the implementation of a simulation model of instruction physical education during the COVID-19 pandemic. They used methods with a quantitative approach and involving level 7 and 8 learners as many as 180 students—random sampling techniques, using questionnaire instruments. Instructional models used by physical education teachers tend to be less varied. This causes the teacher confusion to carry out learning activities in these situations and conditions. After the survey, some teachers are still active in distance learning and continue to communicate with their students. The instructional model used is simulation. Teacher and student communication media using Whatsapp. The aspects assessed during the learning process are affective (social attitude), cognitive, and psychomotor aspects. Communication is the essential point for carrying out learning using distance simulation methods and especially assessment techniques.